Implementasi Hack And Slash Dalam Sistem Pertarungan Game RPG Joko Tingkir - Samudra, Dikdoyo Ganang; Djuniadi, Djuniadi (Edu Komputika Journal, 2017)
Role Playing Game (RPG) is a game’s genre that developed in Japan. The system of this game which is implied in it’s name, is about playing to be someone in many different conditions, times, place, and situations. RPG game’s setting take place around a player that playing as a character or group killing enemies as it travel around world which the story take place. The storyline of RPG maker is very variative and fascinating, it can be everything, for example it can tell about history. This research developing a game that take Joko Tingkir’s history as it storyline and implemented hack and slash battle system. The title of the game is Joko Tingkir. The purpose of this research is to know how to make a RPG game that implement hack and slash battle system to improve it’s quality. The method used in the development of the system is the waterfall method which has requirements analysis, system design, coding, and testing cycle. The result of this research is a RPG game that has implemented hack and slash battle system, that can be used after being tested by using blackbox testing.